а)
![\left \{ {{x-3y=-1} \atop {xy+4y=18}} \right.;\\x=3y-1\\(3y-1)y+4y=18\\3y^2+3y-18=0\\D=9+12*18=225\\y=\frac{-3б15}{6}=\left[\begin{array}{ccc}-3\\2\\\end{array} \left \{ {{x-3y=-1} \atop {xy+4y=18}} \right.;\\x=3y-1\\(3y-1)y+4y=18\\3y^2+3y-18=0\\D=9+12*18=225\\y=\frac{-3б15}{6}=\left[\begin{array}{ccc}-3\\2\\\end{array}](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-3y%3D-1%7D%20%5Catop%20%7Bxy%2B4y%3D18%7D%7D%20%5Cright.%3B%5C%5Cx%3D3y-1%5C%5C%283y-1%29y%2B4y%3D18%5C%5C3y%5E2%2B3y-18%3D0%5C%5CD%3D9%2B12%2A18%3D225%5C%5Cy%3D%5Cfrac%7B-3%D0%B115%7D%7B6%7D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-3%5C%5C2%5C%5C%5Cend%7Barray%7D)
x=-10}} \right. \\\left \{ {{y=2} \atop {x-3*2=-1=>x=5}} \right. \\\end{array}" alt="\left[\begin{array}{ccc}\left \{ {{y=-3} \atop {x-3*(-3)=-1=>x=-10}} \right. \\\left \{ {{y=2} \atop {x-3*2=-1=>x=5}} \right. \\\end{array}" align="absmiddle" class="latex-formula">
Ответ: (-10;-3) и (5;2)
б)
5y=10x-35\\2x^2-10x+35-27=0\\x^2-5x+4=0\\D=25-16=3^2\\x=\frac{5б3}{2}=\left[\begin{array}{ccc}1\\4\\\end{array}" alt="\left \{ {{2x^2-5y=27} \atop {2x-y=7}} \right.\\y=2x-7=>5y=10x-35\\2x^2-10x+35-27=0\\x^2-5x+4=0\\D=25-16=3^2\\x=\frac{5б3}{2}=\left[\begin{array}{ccc}1\\4\\\end{array}" align="absmiddle" class="latex-formula">
y=-5}} \right. \\\left \{ {{x=4} \atop {2*4-y=7=>y=1}} \right. \\\end{array}" alt="\left[\begin{array}{ccc}\left \{ {{x=1} \atop {2*1-y=7=>y=-5}} \right. \\\left \{ {{x=4} \atop {2*4-y=7=>y=1}} \right. \\\end{array}" align="absmiddle" class="latex-formula">
Ответ: (1;-5) и (4;1)